2017
DOI: 10.11606/1413-8050/ea150953
|View full text |Cite
|
Sign up to set email alerts
|

An estimation of the hybrid Phillips curve for Brazil in the inflation targeting regime

Abstract: ResumoO objetivo deste artigo é investigar a dinâmica da inflação no Brasil no período entre 2000-IV e 2014-II, por meio da abordagem da Curva de Phillips híbrida. Essa especificação econométrica permite avaliar os termos forward looking ou expectativa de inflação e backward looking inflação defasada. Os modelos foram estimados pelo método ARDL e os resultados mostraram que a inclusão do custo unitário do trabalho como proxy para a atividade econômica gerou um melhor ajustamento na estimação da Curva de Philli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…This paper is related to other studies that sought to investigate the relationship between unemployment and price inflation in Brazil, as Mendonça & Santos (2006), Oliveira & Feijó (2015), Aragon et al (2016), Triches & Feijó (2017) and Oliveira & Feijó (2017). However, the present paper is based on the original relationship proposed by Phillips (1958), thereby directing our research to the interaction between unemployment rate and wage growth, as Bacha & Lima (2004), Campos et al (2010) e Mendonça et al (2012).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…This paper is related to other studies that sought to investigate the relationship between unemployment and price inflation in Brazil, as Mendonça & Santos (2006), Oliveira & Feijó (2015), Aragon et al (2016), Triches & Feijó (2017) and Oliveira & Feijó (2017). However, the present paper is based on the original relationship proposed by Phillips (1958), thereby directing our research to the interaction between unemployment rate and wage growth, as Bacha & Lima (2004), Campos et al (2010) e Mendonça et al (2012).…”
Section: Introductionmentioning
confidence: 78%
“…In the same sense, Oliveira & Feijó (2017) showed through an inverse quantile regression (IQR) the rising importance of the role played by expectations in the inflation process in Brazil, thus achieving one of the main goals of the Inflation Targeting Regime: the price formation anchored in the economic agents' expectations. According to Triches & Feijó (2017), studies in this field of research have showed that the role played by the inflation expectation is relevant in inflation dynamics and the BACEN is reacting to changes in this variable. Thus, in the case inflation expectations is well anchored in inflation targeting or in any other macroeconomic indicator, the lagged inflation tends to present low persistence.…”
Section: Resultsmentioning
confidence: 99%
“…The assumption in this case is that if the maximum order of series integration (d max ) is added to the Granger model, it can be applied to the non-stationary series level and provide valid estimates [3]. One can specify the proposed one through the bivariate VAR models (z + d max ) comprised by unemployment and independent variables, according to Equation (6) and Equation (7) below:…”
Section: Granger Causality Test Of Toda and Yamamotomentioning
confidence: 99%